(Z)-5-(2, 4-Dihydroxybenzylidene)thiazolidine-2, 4-dione Prevents UVB-Induced Melanogenesis and Wrinkle Formation through Suppressing Oxidative Stress in HRM-2 Hairless Mice. (8th May 2016) - Lee, Bonggi; Moon, Kyoung Mi; Kim, Seong Jin; Kim, So Hee; Kim, Dae Hyun; An, Hye Jin; Jeong, Ji Won; Kim, Ye Ra; Son, Sujin; Kim, Min Jo; Chung, Ki Wung; Lee, Eun Kyeong; et al.
Abstract : Background . Uncontrolled melanogenesis and wrinkle formation are an indication of photoaging. Our previous studies demonstrated that ( Z )-5-(2, 4-dihydroxybenzylidene)thiazolidine-2, 4-dione (MHY498) inhibited tyrosinase activity and melanogenesis in vitro . Objective . To examine in vivo effects of MHY498 as an antiaging compound on UVB-induced melanogenesis and wrinkle formation, we topically applied MHY498 on dorsal skin of HRM-2 hairless mice. Methods . Using histological analysis, we evaluated effects of MHY498 on melanogenesis and wrinkle formation after UVB exposure. In addition, related molecular signaling pathways were examined using western blotting, fluorometric assay, and enzyme-linked immunosorbent assay. Results . MHY498 suppressed UVB-induced melanogenesis by inhibiting phosphorylation of CREB and translocation of MITF protein into the nucleus, which are key factors for tyrosinase expression. Consistently, tyrosinase protein levels were notably reduced in the dorsal skin of the hairless mice by MHY498 treatment. Furthermore, MHY498 inhibited UVB-induced wrinkle formation and collagen fiber destruction by increasing type 1 procollagen concentration and decreasing protein expression levels of MMPs, which play an essential role in collagen fiber degradation. As a mechanism, MHY498 notably ameliorated UVB-induced oxidative stress and NF- κ B activation in the dermal skin of the hairless mice. Conclusion . Our study suggests that MHY498 can be used as a therapeutic or cosmetic agent for preventing uncontrolled melanogenesis and wrinkle formation.